2009
DOI: 10.1093/hmg/ddp034
|View full text |Cite
|
Sign up to set email alerts
|

The SRY-HMG box gene, SOX4, is a target of gene amplification at chromosome 6p in lung cancer†

Abstract: The search for oncogenes is becoming increasingly important in cancer genetics because they are suitable targets for therapeutic intervention. To identify novel oncogenes, activated by gene amplification, we analyzed cDNA microarrays by high-resolution comparative genome hybridization and compared DNA copy number and mRNA expression levels in lung cancer cell lines. We identified several amplicons (5p13, 6p22-21, 11q13, 17q21 and 19q13) that had a concomitant increase in gene expression. These regions were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 41 publications
10
80
0
Order By: Relevance
“…11,[28][29][30] The correlation of high SOX4 expression with poor clinical outcome ( Figure 6D-E) is novel and suggests that SOX4 and SOX4-mediated signaling represent a potential therapeutic target for patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…11,[28][29][30] The correlation of high SOX4 expression with poor clinical outcome ( Figure 6D-E) is novel and suggests that SOX4 and SOX4-mediated signaling represent a potential therapeutic target for patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an acquired stop mutant in the C-terminal serine-rich region of Sox4 (S395X) was found to be associated with a primary lung tumor (Medina et al, 2009). Interestingly, this Sox4 mutant demonstrated enhanced protein expression and, although it was not transcriptionally active, its ectopic expression modulated in vitro transformation of NIH-3T3 cells expressing the weakly oncogenic RhoA-Q63L mutant.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-mediated reduction in Sox4 expression has been shown to correlate with reduced breast cancer metastases in vivo, demonstrating a relation between Sox4 expression levels and cancer progression (Tavazoie et al, 2008). In addition, a recent study described somatic stop mutants of Sox4 in a primary lung tumor, and showed that Sox4 stop mutants associated with transforming ability in vitro and enhanced Sox4 protein levels (Medina et al, 2009). Induction of DNA damage has also been found to control Sox4 protein expression independent of its mRNA transcript levels, suggesting post-transcriptional regulation of Sox4 in response to DNA damage (Pan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We began with a meta-analysis in public lung cancer gene expression databases inquiring if there is any unique expressing pattern among the SOX genes. In this regard, SOX4 was reported as a target of gene amplification in lung cancer (14); more intriguingly, the well-known embryonic regulator SOX2 was recently shown as an amplified lineage-specific survival oncogene for lung and esophagus SQC (15). Aside from these two genes, there has been no evidence linking other SOX family members with lung cancers.…”
mentioning
confidence: 99%